The mental health needs of youth involved in the juvenile justice system in Jordan - Latefa Ali Dardas; Naheel Qaddoura; Amjad Al-Khayat; Bayan Abdulhaq; Mu’taman Jarrar; Mohammad Alkhayat; Ibrahim Aqel (Health & Justice)
Abstract Background Existing evidence elucidates the psychological dimensions of juvenile delinquency, yet the need for cross-cultural validation remains critical to deepen and diversify our understanding of delinquency across different settings. Properly assessing and addressing the mental health needs of youth involved in the justice system (YIJS) is a strategic step that can help design and implement comprehensive responses to produce healthier youth who are less likely to act out and commit crimes. To this aim, this study explored several key mental health dimensions among YIJS who were incarcerated in rehabilitation centers located in Jordan. Methods A paper survey was used to collect data from YIJS who were incarcerated in five rehabilitation centers located in three major provinces in Jordan [Amman (n = 89, 59%), Irbid (n = 50, 33%), and Zarqa (n = 12, 8%)]. A total of 158 YIJS (98% boys) completed the study questionnaire, which included sociodemographic and health measures, as well as measures assessing adolescent depression, anxiety, self-esteem, academic stress, and family relationships. Results Among the surveyed Jordanian YIJS, 36% reported frequent suicide ideation, 57% experienced moderate to severe depressive symptoms, and 13% displayed elevated anxiety levels, while 47% faced high stress levels primarily due to academic pressures. Further, 7% had a family member who attempted suicide, and 5% had a family member who died by suicide. Poor family dynamics were also revealed among YIJS, with about 41% feeling a lack of cohesion, 60.3% encountering frequent conflicts, and 32.8% feeling restricted in expressing themselves openly within their families. Almost 82% reported scores indicating normal self-esteem, 10% low self-esteem, and 8% high self-esteem. Participants with high self-esteem exclusively reported theft, whereas drug use was the most common offense among those with low self-esteem. Depression scores were significantly related to self-esteem and educational stress scores. Conclusions Jordanian YIJS are particularly vulnerable and under studied population. This study assists with addressing a critical evidence gap concerning the mental health needs of incarcerated youth residing outside the regularly studied context of high-income countries. The findings call for a comprehensive, culturally adapted approach that includes enhancing the juvenile justice system’s focus on mental health services, educational support, and family engagement. Our study supports the adoption of the National Strategy for Juvenile Justice (2024–2028), which aims to foster a more rehabilitative and child-friendly justice system in Jordan. This approach not only aligns with global human rights standards but also addresses the specific needs and circumstances of Jordanian youth, promoting their overall well-being and reducing recidivism.